Dziennik malarski jako fenomen artystyczno-psychologicznego wyrazu i oddziaływania - Żyżniewski, Daniel Jerzy (Strategie komunikacyjne i procesy twórcze, 2022)
Some basic mechanisms between perception, thinking and mood with artistic process of creation are described in this article. Main aspects of cognitive-behavioral reception of reality and its meaning for dynamic of creative energy are explained in this article. Some basic terms taken from Mindfulness therapeutic techniques including guided meditation technique are outlined in the context of brain activity. Dependencies between Mindfulness techniques with cognitive behavioral ones and painting creativity are also outlined in this article. The Painting diary created by Weronika Naszarkowska-Multanowska is described as a painting work and simultaneously as a self-therapeutic technique, which meets some of the psychological help criteria. In this article the painting diary is described as a tool of social communication and mood regulation in low energy of artistic creativity. The painting diary is presented as multilayer medium of interdisciplinary forms of expression and influence, which agency is seen not only in artist’s life, but also in audiences.